An open-label forearm-controlled pilot study to assess the effect of a proprietary emollient formulation on objective parameters of skin function of eczema-prone individuals over 14 days - Wakeman MP (Dove Medical Press, 2017)
Michael Paul Wakeman Department of Cancer Sciences, School of Medicine, University of Birmingham, Edgbaston, Birmingham, UK Background: This study examines the efficacy of a new plant-based emollient and assesses product acceptability.Methods: Primary efficacy endpoints were improvement in transepidermal water loss, hydration, skin elasticity and firmness, erythema, and skin roughness and smoothness as measured using the versions of Tewameter, Corneometer, Cutometer, Mexameter, and Visioscan VC98, respectively. The cream was applied twice daily by 32 participants to an area of one forearm unaffected by eczema, while the same area of the other forearm was used as a control. Measurements were taken at day 0 and day 14. Secondary endpoints assessed the acceptability of the product.Results: At the end of 2 weeks, transepidermal water loss, hydration, skin elasticity and firmness, erythema, and skin roughness and smoothness improved. All changes were statistically significant (p<0.01). The rate of satisfaction with the emollient properties was 82%, and the rate of absorption into the skin was 88%. Results show that the emollient hydrates and repairs eczema-prone skin with high levels of acceptability. Keywords: eczema, Suvex, moisturizer, emollient, hydration, skin barrier function